A prospective study revealing a compounded burden of COVID-19, sex, and clinical diagnosis of alcohol use disorder and HIV infection on quality of life, anxiety, and alcohol use. (August 2022) - Lannoy, Séverine; Fama, Rosemary; Sassoon, Stephanie A.; Le Berre, Anne-Pascale; Asok, Priya; Zahr, Natalie M.; Pfefferbaum, Adolf; Sullivan, Edith V.
Abstract: The COVID-19 pandemic led to unprecedented restrictions to mitigate disease spread, leading to consequences affecting mental health. Many studies examining COVID-19 pandemic effects on well-being and mental health initiated inquiry after the pandemic onset, whereas we used self-report questionnaires obtained before the pandemic to re-assess the same functions during the pandemic. Participants were drawn from our ongoing longitudinal studies of people with HIV infection, alcohol use disorder (AUD), HIV + AUD comorbidity, and controls. We used phone or mail contact to invite all to participate in our COVID phone survey, which included three self-report questionnaires: Health-related Quality of Life (QoL), State-Trait Anxiety Inventory (STAI), and Alcohol Use Disorder Identification Test (AUDIT). Of 218 eligible participants, 86 responded (July 2020–March 2021): clinical (29 men, 23 women; 17 AUD, 21 HIV, 14 HIV + AUD); control (17 men, 17 women). QoL scores declined, and anxiety symptoms increased from pre-COVID surveys in all groups; clinical women reported greater negative changes than the other groups. QoL subscales revealed COVID-related declines in emotional well-being in all groups, with clinical women reporting additional declines in energy, physical and social functioning, health, and pain increase. Clinical men also reported health declines. Although AUDIT scores were stable in all groups between assessments, changes in AUDIT scores were inversely correlated with QoL scores in clinical women; in clinical men, changes in STAI scores were inversely correlated with QoL scores. Although all groups were adversely affected by the pandemic, the negative effects were greater in the clinical group regardless of diagnosis and greatest in clinical women. Highlights: Quality of life, anxiety, and alcohol use were surveyed before and during COVID-19. Responders were 29 men and 23 women with clinical diagnoses and 34 controls. QoL scores declined and anxiety symptoms increased in all groups. Greater alcohol use correlated with poorer QoL in clinical women. Negative effects were greater in the clinical group, especially clinical women.